PENERAPAN METODOLOGI STRUCTURED ANALYSIS AND DESIGN TECHNIQUES (SADT) PADA REKAYASA SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) RUKUN WARGA 36 KELURAHAN BAHAGIA, BEKASI - Hartati, Tri; Hikmah, Noer; Purwanto, Heru (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Building and developing information systems is a step to improve system performance which was initially carried out manually with most activities relying on human capabilities. Improving the system towards a better direction cannot be separated from the role of information technology so that information system engineering can be carried out optimally. Likewise with the population system that runs in Rukun Warga 36, ​​Bahagia Village, Bekasi, where resident administration activities are still carried out manually using paper and pen. This of course causes problems in the future, such as storage space for files piling up, vulnerability to data loss, data search processes that take time, and so on. By analyzing the obstacles experienced, population administration information system engineering is the right solution to improve the manual system. The methodology used in this research is Structured Analysis and Design Techniques (SADT) using activity diagrams as a depiction of information system activities. The expected research result is the development of a population administration information system that is useful for village administrators in Rukun Warga 36, ​​Bahagia Village, Bekasi.